Rational Microstructure Design on Metal–Organic Framework Composites for Better Electrochemical Performances: Design Principle, Synthetic Strategy, and Promotion Mechanism. Issue 3 (20th January 2020) - Li, Zhaoqiang; Ge, Xiaoli; Li, Caixia; Dong, Shihua; Tang, Rui; Wang, Chengxiang; Zhang, Zhiwei; Yin, Longwei
Abstract: Metal–organic frameworks (MOFs) simultaneously containing metal ions and organic ligands have recently shown great potential for application in energy storage and conversion fields due to their controllable conversion into carbon materials or various metal species, which often exhibit superior electrochemical performance as electrode materials for energy storage and conversion. Nevertheless, the electrochemical energy storage performance of MOF derivatives can still be further enhanced through building composites with other functional materials. It is of great significance in developing new strategies of fabricating MOF composites to achieve electrode materials with improved charge transfer and electrochemical redox reaction kinetics. In this review, the novel design and strategies of MOF composites with various functional components are focused on, including carbon‐based materials (carbon nanotubes, graphene, etc.), metal oxides, 3D conductive substrates, polymeric materials, and the second MOFs and metal salts, especially their derivatives for energy storage and conversion fields. The key factors for controllable synthesis of various MOF composites and electrochemical performance enhancement mechanisms are discussed in detail. It is expected that this review will provide new inspiration for the development of MOF derivatives for energy storage and conversion. Abstract : A comprehensive summary of metal–organic framework (MOF) composites with various functional materials is provided, including carbon materials, metal chalcogenides, polymers, nickel foam, the secondary MOFs, and so on. The design principle, synthetic strategy, and the promotion mechanism for the electrochemical performance are presented. Current challenges and future perspectives are outlined.